2010
DOI: 10.1099/mic.0.041780-0
|View full text |Cite
|
Sign up to set email alerts
|

Genes required for the synthesis of heptose-containing oligosaccharide outer core extensions in Haemophilus influenzae lipopolysaccharide

Abstract: Heptose-containing oligosaccharides (OSs) are found in the outer core of the lipopolysaccharide (LPS) of a subset of non-typable Haemophilus influenzae (NTHi) strains. Candidate genes for the addition of either L-glycero-D-manno-heptose (LD-Hep) or D-glycero-D-manno-heptose (DD-Hep) and subsequent hexose sugars to these OSs have been identified from the recently completed genome sequences available for NTHi strains. losA1/losB1 and losA2/losB2 are two sets of related genes in which losA has homology to genes e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…R2866_0112 was found to contribute most significantly to survival of NTHi strain R2866 in the presence of active complement, which was in accordance with our previous genome‐wide mariner transposon mutants screen with genomic array footprinting (GAF) as read‐out (Langereis et al ., ). Other genes ( lgtF , lgtC , losB2 , lic2A , neuA , siaP , siaT and mlaE ) that were identified in our screen, were earlier found to be involved in resistance to complement‐mediated killing (Hood et al ., 1999; 2004; 2010; Ho et al ., ; Nakamura et al ., ; Morey et al ., ). Furthermore, two genes were identified for which a role in complement resistance was not established previously ( lapB [ R2866_1281 ] and clpB [ R2866_1533 ]).…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…R2866_0112 was found to contribute most significantly to survival of NTHi strain R2866 in the presence of active complement, which was in accordance with our previous genome‐wide mariner transposon mutants screen with genomic array footprinting (GAF) as read‐out (Langereis et al ., ). Other genes ( lgtF , lgtC , losB2 , lic2A , neuA , siaP , siaT and mlaE ) that were identified in our screen, were earlier found to be involved in resistance to complement‐mediated killing (Hood et al ., 1999; 2004; 2010; Ho et al ., ; Nakamura et al ., ; Morey et al ., ). Furthermore, two genes were identified for which a role in complement resistance was not established previously ( lapB [ R2866_1281 ] and clpB [ R2866_1533 ]).…”
Section: Resultsmentioning
confidence: 98%
“…Twenty‐four out of 57 genes identified in the previous GAF analysis were found to be attenuated at least twofold with a P < 0.01 in the Tn‐seq analysis. Various genes related to LOS biosynthesis ( lgtF , lgtC , losB2 and lic2A ), incorporation of sialic acid in the LOS structure ( neuA , siaP and siaT ) and phospholipid ABC transporter permease component ( mlaE ) that were previously shown to be involved in resistance to complement‐mediated killing (Hood et al ., 1999; 2004; 2010; Ho et al ., ; Nakamura et al ., ; Morey et al ., ) were identified in this screen, which shows the power of this genome‐wide screening technique. The role for the genes lapB ( R2866_1281 ) or clpB ( R2866_1533 ) in resistance to complement‐mediated killing is currently not known.…”
Section: Discussionmentioning
confidence: 98%
“…Previously, two genes losB1 and losB2 were found, which are responsible for addition of D,D-Hep or L,D-Hep, respectively (44). These two genes were found alongside losA1, losA2 genes encoding glycosyltransferases that are responsible for substitution of the external heptose (116). DNA sequence analyses indicated that strains 1158/1159 have losA2/losB2 and, however instead of losA1/losB1 they have lic2B/lic2C gene pairs.…”
Section: Scheme 3 Structure Proposed For the Hep 4 Glycoforms Of Nthmentioning
confidence: 99%
“…More likely that despite the high degree of homology between losB2 from 1158 and losB2 from R2846 and 1207, the function of 1158LosB2 is more closely related to the function of LosB1 in the other NTHi strains (116). Giving the small amount of 6-substituted D,D-Hep observed by methylation analysis, it is possible that LosB2 in 1158 may still possess low level activity to add L,D-Hep to β-D-Glcp linked to HepI .…”
Section: Scheme 3 Structure Proposed For the Hep 4 Glycoforms Of Nthmentioning
confidence: 99%
“…Hybridization using an lgtF probe confirmed its presence in all our isolates. Further extension from glucose I occurs at its O-4 position in strains containing lex2B encoding a glucosyl-or galactosyl-specific transferase (8) and at its O-6 position in strains with losB1 or losB2 encoding a heptosyltransferase (heptose IV) (9). lex2B was present in 73% of our NTHi strains and the majority (47/60) were predicted to express a glucose-specific allele.…”
mentioning
confidence: 99%